The Effects of Social Media on Mental Health Among Adolescents - Li, Shengwei (Transactions on Materials, Biotechnology and Life Sciences, 2024)
This study delves into the intricate relationship between social media and adolescents’ mental health, a pressing concern in the digital era. The development of social media is a product of the times and a reflection of social progress. For individuals, the impacts are diverse. Social media platforms, while promoting social interaction and a sense of belonging, also harbor dangers like addiction and cyberbullying that can negatively impact self-esteem and mental health. The paper offers a succinct literature review, emphasizing social media’s dual impact as a source of support and stress for high school students. It highlights the pivotal role of mental well-being in countering social media’s negative influences and advocates for additional research to develop strategies that encourage positive social media engagement. The study concludes with a call for a balanced strategy to maximize social media’s benefits for adolescents while protecting them from its potential detriments. This study explores the relationship between social media and the mental health of adolescents, a pressing issue in the digital age. The development of social media is a product of the times and a reflection of social progress. There are both positive and negative consequences for individuals. While social media platforms promote social interaction and a sense of belonging, they also pose dangers such as addiction and cyberbullying, which can harm self-esteem and mental health. The paper provides a concise review of the literature, emphasizing the dual impact of social media as a source of support and stress for students. It highlights the central role of mental well-being in countering the negative influences of social media and advocates for further research to develop strategies to promote positive social media engagement. The study concludes with a call for a balanced strategy to maximize the benefits of social media for young people while protecting them from its potential harm.